PENGARUH TIPE KEPRIBADIAN, PENGALAMAN DAN PENERIMAAN PERILAKU DISFUNGSIONAL TERHADAP AUDIT JUDGMENT (STUDI PADA KANTOR AKUNTAN PUBLIK MALANG) - Ervina Wafi Rokhmani; Anik Malikah; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study was to analyze the effect of personality type,experience and dysfunctional behavior on audit judgment in Malang PublicAccountants Office offices. The Public Accounting Firm (KAP) located inMalang City, East Java. This method uses purposive sampling with a sample of65 respondents.This study uses primary data obtained through questionnaires.To examine the relationship of personality type, experience of dysfunctionalbehavior and audit judgment, multiple linear regression test through softwarespss Ver 18. The results showed that personality type, experience, behavioralacceptance of dysfunctional behavior towards variables have significant effectson audit judgment.Keywords: personality type, experience and acceptance of dysfunctionalbehavior towards judgment